1999
DOI: 10.1161/01.atv.19.6.1549
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Platelet Deposition and Activation in Models of Injured Vessel Wall Ensure Optimal Neutrophil Adhesion Under Flow Conditions

Abstract: Abstract-Platelets at injured vessel wall form an adhesive surface for leukocyte adhesion. The precise relation between platelet adhesion and activation and leukocyte adhesion, however, is not known. We therefore used various models of injured vessel wall to form different patterns of platelet adhesion. The interaction of polymorphonuclear neutrophils (PMNs) was subsequently studied under flow conditions. In the absence of platelets, not only endothelial cell, smooth muscle cell, and fibroblast matrices but al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
0
19
0
2
Order By: Relevance
“…In fact, P-selectin expressed by surface-adherent activated platelets has been demonstrated to trigger significant leukocyte recruitment under flow even at a low density of surface coverage. 23 We observed here that, together with leukocytes, substantial numbers of platelets attached to inflamed HUVEC after exposure to arterial shear stress. Importantly, leukocyte adhesion strictly colocalized with platelet adhesion, whereas few leukocytes were recruited to areas devoid of adherent platelets.…”
Section: Discussionmentioning
confidence: 56%
“…In fact, P-selectin expressed by surface-adherent activated platelets has been demonstrated to trigger significant leukocyte recruitment under flow even at a low density of surface coverage. 23 We observed here that, together with leukocytes, substantial numbers of platelets attached to inflamed HUVEC after exposure to arterial shear stress. Importantly, leukocyte adhesion strictly colocalized with platelet adhesion, whereas few leukocytes were recruited to areas devoid of adherent platelets.…”
Section: Discussionmentioning
confidence: 56%
“…41,42 In a recent study, we have shown that the mural thrombus in human atherosclerotic aneurysms is a site of storage and release of MMP-9 and that polymorphonuclear leukocytes trapped within the thrombus are the main cellular source of this MMP-9. 22 Recent luminal clots are sites of platelet deposition 43 and fibrin-fibronectin copolymerization, 44 and represent an optimal substrate for PMN adhesion. In the present work, we have extended these data using an ex vivo approach to study proteases bound to and released by the mural thrombus in human aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet P-selectin guarantees the access of leukocytes to perivascular tissues even when dying or severely damaged endothelial cells fail to sustain leukocyte rolling and adhesion. 15,16 Indeed, endothelial cells surrounding the lesion release signals that amplify the expression of P-selectin on adhering platelets. 17 The P-selectin-dependent interaction of neutrophils and platelets amplifies mutually, promoting the exchange of metabolites and protecting released molecules from plasma inhibitors.…”
Section: Introductionmentioning
confidence: 99%